Behavior of Newborns Weighing less than 1 800 g - Betsy Rodríguez González; Jorge Luis Felpeto Fuentes (Medisur)
Introduction: despite the resources made available in Public Health to care for newborn infants, low birth weight indicators remain elevated in these infants. Objective: to identify what is the behavior of infants less than 1 800 grams.¨ Enrique Cabrera Hospital ¨. Methods: we performed a longitudinal retrospective study and Enrique Cabrera Hospital during the period February 2007 to December 2008, we studied 45 infants weighing less than 1800 grams, who were admitted consecutively. Biological variables were analyzed: incidence, diseases that lead to ventilation, stay, cause of death and status at discharge. Information was collected from medical records and service statistics, the data were processed using descriptive statistics, and used to calculate percentages in tables exposing. Results: of the 8 012 45 newborns (0,56%) were underweight (<1 800g) fans, 24,4%, with an incidence of 0,13%, the group of 32 to 36 weeks accounted for 64, 4%, 75,6% were between 1 weight 402g to 1 800g and males with 55.5%, the causes of death were sepsis and intraventricular hemorrhage with 33,3% survival was obtained 86,6%. Conclusion: the incidence of low weight and ventilation was poor, a predominance of males, the weight group of 1 402 to 1 800 g, gestational age from 32 to 36 weeks and within the main causes of death were sepsis and intraventricular hemorrhage, and survival was obtained properly.